Research of the indirect friction sensor for prediction of contact stress by improved inverse method in strip rolling. (30th August 2017) - Li, Si; Wang, Zhigang; Ruan, Jinhua; Liu, Changming; Xu, Zengbing
Abstract: In order to avoid strip marks or perturbation of local lubricant flow at the interface between strip and work roll in strip rolling, an indirect friction sensor has been designed. This sensor is based on the inverse method improved by envelope fitting method, which utilizes strain gage to measure strains at one point inside the work roll to evaluate the contact stress in roll gap. Then several cold rolling tests have been performed at different reductions to demonstrate the rational and the validity of this indirect friction sensor. Comparing the results evaluated by finite element method with the results reconstructed by different inverse methods, it is found that the improved inverse method leads to a better solution to evaluation of the contact stress, in particular for prediction of shear stress. In addition, reasonable prediction is obtained for large reduction but not for small reduction (only the order of magnitude is obtained). It is believed that this research has a strategic importance for practical application.